In Vitro Phagocytosis of Myelin Debris by Bone Marrow-Derived Macrophages - Rolfe, Alyssa J (J Vis Exp, 2017)
Bone marrow-derived macrophages (BMDMs) are mature leukocytes that serve a critical physiological role as professional phagocytes capable of clearing a variety of particles. Normally, BMDMs are restricted from the central nervous system (CNS), but following an injury, they can readily infiltrate. Once within the injured CNS tissue, BMDMs are the primary cell type responsible for the clearance of injury-derived cellular debris, including large quantities of lipid rich myelin debris. The neuropathological ramifications of BMDM infiltration and myelin debris phagocytosis within the CNS are complex and not well understood. The protocols described here, allow for the direct in vitro study of BMDMs in the context of CNS injury. We cover murine BMDM isolation and culture, myelin debris preparation, and assays to assess BMDM myelin debris phagocytosis. These techniques produce robust quantifiable results without the need for significant specialized equipment or materials, yet can be easily customized to meet the needs of researchers.